How Does the State Regulate the Administration of Unregistered Marriages in Muslim Minority Communities? The Practice of Mass Weddings in Jayapura City - Rahman, Encep Taufik; Suganda, Ahmad; Lousada, Sérgio António Neves; Khafidz, Hasanah Abd; Huda, Miftakhul; Sopyan, Yayan; Mutmainah, Naeli; Kirin, Arwansyah Bin; Sartono, Sartono; Shapiulayevna, Aliyeva Patimat (Jurnal Ilmiah Al-Syir'ah, 2024)
This study aims to analyze how the state regulates the administration of unregistered marriages (nikah sirri) in Muslim minority communities in Jayapura City, with a focus on the practice of mass weddings organized to facilitate the registration of marriages. Unregistered marriages, which are not recorded by the state, are still found among Muslim minorities in Jayapura. Factors influencing the practice of unregistered marriages include economic limitations, lack of awareness about administrative procedures, and difficulty in accessing official marriage registration services. To address these issues, the Jayapura City government, through the Religious Affairs Office (KUA), the Religious Court (PA), and the Directorate General of Population and Civil Registration (DUKCAPIL), has initiated a mass wedding program aimed at simplifying the legalization process for couples who have not yet registered their marriages. This research uses a qualitative approach with interviews and observations of couples participating in the mass wedding program. The findings indicate that this program is effective in raising public awareness about the importance of marriage registration. However, challenges remain in terms of legal understanding and the readiness of couples to comply with the applicable administrative procedures. The study suggests the need for increased education about the importance of marriage administration and strengthening access to marriage registration services to reduce the practice of unregistered marriages. With the mass wedding program, it is hoped that all marriages in Jayapura City can be legally registered according to state law, providing optimal legal protection for married couples